In Silico Study of Bioactive Compounds from Cinchona Bark as Potential Antimalarial Against Human Glucokinase Receptor - Kezia Stella Carmencinta Salvi; Alifa Dhia Shalima; Alya Novia Hanifa; Johnessa Cung; Bagus Adhinagoro; Shela Salsabila; Muchtaridi (Prodi Kimia, 2025)
Malaria remains a significant health concern in Indonesia, with endemic regions reporting persistent transmission of Plasmodium parasites. This study explores the potential of compounds derived from Cinchona succirubra, traditionally known for its antimalarial properties, using a comprehensive in silico approach. Utilizing Lipinski’s prediction, ADME-Tox, pharmacophore screening, and molecular docking techniques, we assessed the pharmacological potential of its compounds against glucokinase enzymes. Through 10 alkaloid compounds taken from the bark of the cinchona tree, among which the one that gives the best results in its role on the receptor is mefloquine. The result showed that mefloquine had a BE of -3.95 kcal/mol, an inhibition constant of 1.27 μM, but no interactions with any important amino acid residues. The HIA and CaCo-2 values were 93.737% and 22.686 nm/sec, respectively, whereas the PPB and BBB values were 74.270% and 74.270%. Neither is this substance carcinogenic or mutagenic. Low binding energy and the most favored interaction with the receptor were observed for mefloquine. Thus, mefloquine exhibits potential as a prospective glucokinase inhibitor.